2016
DOI: 10.1177/0268355515613740
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy complications of peripheral venous malformations

Abstract: Background Sclerotherapy is often the primary treatment for peripheral venous malformations. It is mostly sufficient alone, but can be combined with other endovascular techniques. Despite its mini-invasiveness, it is not without potentially severe complications. Here, we systematically report sclerotherapy complications in trunk and extremity venous malformations. Methods We retrospectively assessed the complications of 127 consecutive patients who had received sclerotherapy for peripheral venous malformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…Major complications are reported in 10-30 % [33]. Another recent study by Aronniemi et al showed an overall complication rate per procedure of 12.5 % [34]. Common complications of sclerotherapy include nerve [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major complications are reported in 10-30 % [33]. Another recent study by Aronniemi et al showed an overall complication rate per procedure of 12.5 % [34]. Common complications of sclerotherapy include nerve [24].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of procedures were carried out with the patient under general anaesthesia. If the patients were older and able to understand the procedure, local or none anaesthesia was fi rst choice in the treatment of VMs [18]. Fluid-fi lled venous spaces were cannulated with 20-gauge or 21-gauge needles under ultrasound guidance [19].…”
Section: Sclerotherapy Of Vascular Malformationsmentioning
confidence: 99%
“…Berenguer and colleagues reported a 50% rate of adverse reactions to sclerotherapy of craniofacial VM with anhydrous ethanol. Aronniemi and colleagues compared sclerosants in the treatment of peripheral VM and found a greater risk of local complications in subcutaneous lesions with ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of MDA was assessed intraoperatively, using the above-described sonographic features of successful ablation, and with the same diagnostic modality at follow ups [35,36]. In contrast to foam sclerotherapy, in which the extent of ablation is rather unpredictable, MDA enables precise closure of target veins [37][38][39]. Without tumescence the distance between the tip of the needle inserted to the subfascial part of perforator and the deep veins is approximately 3-4 mm, after tumescence this distance increases to 10-15 mm.…”
Section: Discussionmentioning
confidence: 99%